Applying max-sum to teams of mobile sensing agents. (May 2018) - Yedidsion, Harel; Zivan, Roie; Farinelli, Alessandro
Abstract: Multi-agent applications that include teams of mobile sensing agents are challenging since they are inherently dynamic and a single movement of a mobile sensor can change the problem that the entire team is facing. A variation of the Distributed Constraint Optimization model for Mobile Sensor Teams (DCOP_MST) was previously adjusted to represent such problems along with local search algorithms that were enhanced with exploration methods. This paper considers the use of the Max-sum algorithm for solving problems of deploying a mobile sensor team in an unknown environment to track and monitor points of interest (targets), represented by the DCOP_MST model. The DCOP_MST model allows the representation of different functions for aggregating the joint coverage of targets by multiple sensors. The use of different functions has a dramatic effect on the complexity of the Max-sum algorithm. When using cardinality functions, Max-sum can be performed efficiently regardless of the arity of constraints. When Max-sum is used to solve applications that require other (more complex) aggregation functions, its complexity is exponential in the arity of the constraints and thus, its usefulness is limited. In this paper we investigate the performance of the Max-sum algorithm on two implementations of the DCOP_MST model. Each implementation considers a different joint credibility function for determining the coverage for each target, with respect to the locations and the credibility of agents. In the first, the coverage is calculated according to the number of agents that are located within sensing range from the target. This function can be calculated efficiently. The second takes the angle between the lines of sight of different agents to a target into consideration. The larger the difference in the angle between the lines of sight, the higher the coverage efficiency. We analyze the challenges in adjusting the Max-sum algorithm in both scenarios and propose enhancements of the algorithm that make it more efficient. We provide empirical evidence of the advantages resulting from these enhancements in comparison to the naive algorithm.